STUDI BIOFASIES FORAMINFERA BESAR DI BATUAN KARBONAT FORMASI RAJAMANDALA BERUMUR OLIGOSEN AKHIR-MIOSEN AWAL DAERAH PADALARANG, JAWA BARAT - Irwansyah
The Rajamandala Formation in Padalarang, West Java consists mostly of limestone that was deposited during Late Oligocene to lower part of Early Miocene age. This formation contains organism mainly larger foraminifera, coral and algae which need specific ecological condition to grow. In this study, larger foraminifera and non foram fossil from the Rajamandala Formation are identified and characterized for carbonate facies modeling. A total of 70 outcrop samples have been collected that represent various carbonate facies of the Rajamandala Formation. Based on petrographic study these samples can be grouped into six facies related with six standard facies belt of Wilson (1975). Larger foraminifera contents and their association are examined with multivariate analysis (cluster analysis, indicator value and principal componen analysis) to determine biofacies and indicator fauna/taxa that characterized different facies. The results of this study are as follows: (1) open sea shelf facies is characterized by planktonic foraminifera, (2) deep shelf margin facies is characterized by planktonic foraminifera, Cycloclypeus, Operculina, Heterostegina, Amphistegina and Spiroclypeus, (3) foreslope facies is characterized by Lepidocyclina, Miogypsinoides, Pararotalia and Spiroclypeus, (4) organic buildup facies is characterized by coral, (5) open platform facies is characterized by Quinqueloculinids group (indeterminate Quinqueloculinids and Austrotrillina), Pararotalia, coral and algae, (6) restricted platform/lagoon facies is characterized by Quinqueloculinids group (indeterminate Quinqueloculinids and Austrotrillina) and Borelis.